Differences in natural killer cell numbers between elite kayakers and non-athletes - Borges, G. F.; Rama, L.; Rosado, F.; Alves, F.; Sntos, A.; Gomes, B.; Massart, A.; Pedreiro, S.; Paiva, A.; Teixeira, A. M. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Prolonged strenuous exercise has been associated with a depression of immune function. At rest immune function in athletes compared with non-athletes has more similarities than disparities. However, there is a need for more studies that specify subsets and relates to specific times of the training. Aim: The objective of this study was to see if chronic training was able to produce sustained differences in the peripheral blood cells in leukocytes subpopulations (WBC, granulocytes, monocytes, total lymphocytes, B and T lymphocytes, CD4+ and CD8+ T cels and NK cells) of athletes (kayakers) after a rest period of 6 weeks when compared to non-athletes. Methods: The sample comprised 13 elite male kayakers, 20±3 years old, 75.0±7.9kg weight and 177.3±7.1cm stature. Their VO2max was 58.3±7.8 ml/kg/min. The non-athlete group comprised 7 healthy males, aged 18±1 years old, 81.3± 13.8 kg of weigh and 171.9±4.5cm stature. The athlete blood samples were collected at the beginning of the training season, after an off period of six weeks of training. To verify the differences between the athlete and non-athlete groups the Mann-Whitney U Test was used, and significance was set at P<0.05. Results: No differences between the trained kayakers and the non-athletes were found at rest except for the total number and percentage of NK cells, namely in the CD3-CD56+CD8+ subset whose values were lower in the athletes. Discussion: Our results seem to confirm that a reduction in NK cell numbers, especificaly in CD56+CD8+ subset even for longer periods of time. During exercise the number of circulating NK cells in the peripheral blood increases after one to two hours and then reduce to values that may be below the baseline (Del Giacco et al., 2001). The reduction in NK cell counts has been reported to persisted for up to seven days following exercise (Shek et al., 1994). The lower peripheral blood NK cell counts, especially CD3-CD56+CD8+ subset, in elite atlhetes may relate to reduced cellular production and cytotoxicity. On the other hand, this finding may reflect a chronic adaptation to training, suggesting that a decrease in the number of CD3-CD56+CD8+ cells could mean a lower risk of lysing autologous cells and decrease the inflammation status together with a redistribution of the NK cells into tissues for immune surveillance.